What after Java? From objects to actors - Varela, Carlos A.; Agha, Gul A. (Computer networks and ISDN systems, 1998)
In this paper, we discuss some drawbacks of the Java programming language, and propose some potential improvements for concurrent object-oriented software development. In particular, we argue that Java's passive object model does not provide an effective means for building distributed applications, critical for the future of Web-based next-generation information systems. Specifically, we suggest improvements to Java's existing mechanisms for maintaining consistency across multiple threads (e.g. synchronized), sending asynchronous messages (e.g. start/run methods) and controlling resources (e.g. thread scheduling). We drive the discussion with examples and suggestions from our own work on the Actor model of computation.